An electrochemical biosensor for the detection of pathogenic bacteria based on dual signal amplification of Cu3(PO4)2-mediated click chemistry and DNAzymes. Issue 15 (5th July 2021) - Wei, Hongguo; Bu, Shengjun; Zhang, Wenguang; Ma, Li; Liu, Xiu; Wang, Ze; Li, Zhongyi; Hao, Zhuo; He, Xiuxia; Wan, Jiayu
Abstract : A novel electrochemical biosensor for detecting pathogenic bacteria was designed based on specific magnetic separation and highly sensitive click chemistry. Abstract : A novel electrochemical biosensor for detecting pathogenic bacteria was designed based on specific magnetic separation and highly sensitive click chemistry. Instead of enzyme–antibody conjugates, organic–inorganic hybrid nanoflowers [concanavalin A (Con A)–Cu3 (PO4 )2 ] were used as the signal probe of the sandwich structure. The inorganic component, the copper ions of hybrid nanoflowers, was first used to amplify signal transduction for enzyme-free detection. Sodium ascorbate could dissolve Cu3 (PO4 )2 of the signal probe to produce Cu 2+, which was subsequently converted to Cu +, triggering the Cu + -catalyzed alkyne–azide cycloaddition (CuAAC) reaction between azide-functionalized ssDNA (a fragment of the DNAzyme-containing sequence) and alkyne-functionalized ssDNA immobilized onto the electrode surface. As a result, the DNAzyme was immobilized onto the gold electrode, which produced a positive and stable electrical signal. An exceptional linear relationship was observed between the electrical signal and the concentration of Salmonella typhimurium (10 1 –10 7 CFU mL −1 ) with a detection limit of 10 CFU mL −1 . The developed electrochemical biosensor based on dual signal amplification of Cu3 (PO4 )2 -mediated click chemistry and DNAzymes exhibited good results in detecting S. typhimurium in milk samples.